Controlled non‐randomised before–after study evaluating the impact of a focused recommendation card on vaccination rates of oncological patients—The Easy Vaccination in Oncology (EVO) strategy. (11th October 2022) - Kiderlen, Til R.; Trostdorf, Katrin; Delmastro, Nicola; Salomon, Arne; Scholz, Christian W.; Späth‐Schwalbe, Ernst; Mansmann, Veit; Roll, Stephanie; Reinwald, Mark; de Wit, Maike
Abstract: Objective: By implementing a focused must‐have vaccination strategy (Easy Vaccination in Oncology [EVO]), we aimed to increase rates for high‐impact vaccinations ( Streptococcus pneumoniae, influenza, herpes zoster and hepatitis B) in the at‐risk population of oncological patients. Methods: In this German multicentre interventional non‐randomised controlled two‐arm open trial with repeated cross‐sectional data collection, we evaluated the EVO strategy as an easy to implement approach. Vaccination rates were assessed in the outpatient setting and re‐assessed after 3 months. A generalised linear mixed model (GLMM) was used to assess the primary endpoint ( Streptococcus pneumoniae vaccination rates according to recommendations), taking clustering within clinics into account. Results: Vaccination rates substantially increased in the intervention group; Streptococcus pneumoniae +21.5% (+16.7% according to recommendations), influenza +12.2%, herpes zoster +13.3% (+13.6% age group 50+), and hepatitis B +11%. Vaccination rates in the control group tended to decrease or increase only moderately (−5.8% [−3.8%], +7.4%, +2.1% [1.4%], and −1.7%, respectively). GLMM showed significant effect of the intervention (OR 7.50, 95% CI 2.18–25.80, p = 0.001). Conclusion: This easy‐to‐implement and resource‐saving approach has the potential to increase vaccination rates in oncological patients and to have a considerable impact protecting oncological patients from preventable infectious diseases. Clinical trial registration: The study was registered at the German Resister for Clinical Studies (DRKS) under DRKS00020118.